The Interactive Role of Hydrocarbon Seeps, Hydrothermal Vents and Intermediate Antarctic/MediterraneanWater Masses on the Distribution of Some Vulnerable Deep-Sea Habitats in Mid Latitude NE Atlantic Ocean - Somoza, Luis (2021)
In this work, we integrate five case studies harboring vulnerable deep-sea benthic habitats in different geological settings from mid latitude NE Atlantic Ocean (24–42º N). Data and images of specific deep-sea habitats were acquired with Remoted Operated Vehicle (ROV) sensors (temperature, salinity, potential density, O2, CO2, and CH4). Besides documenting some key vulnerable deep-sea habitats, this study shows that the distribution of some deep-sea coral aggregations (including scleractinians, gorgonians, and antipatharians), deep-sea sponge aggregations and other deep-sea habitats are influenced by water masses’ properties. Our data support that the distribution of scleractinian reefs and aggregations of other deep-sea corals, from subtropical to north Atlantic could be dependent of the latitudinal extents of the Antarctic IntermediateWaters (AAIW) and the Mediterranean Out- flow Waters (MOW). Otherwise, the distribution of some vulnerable deep-sea habitats is influenced, at the local scale, by active hydrocarbon seeps (Gulf of Cádiz) and hydrothermal vents (El Hierro, Canary Island). The co-occurrence of deep-sea corals and chemosynthesis-based communities has been identified in methane seeps of the Gulf of Cádiz. Extensive beds of living deep-sea mussels (Bathymodiolus mauritanicus) and other chemosymbiotic bivalves occur closely to deep-sea coral aggregations (e.g., gorgonians, black corals) that colonize methane-derived authigenic carbonates.